2013
DOI: 10.7314/apjcp.2013.14.8.4743
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated with Osteoporosis among Korean Cancer Survivors: A Cross-Sectional Analysis of the Fourth and Fifth Korea National Health and Nutrition Examination Surveys

Abstract: Background: Identifying and managing osteoporosis among cancer survivors is an important issue, yet little is known about the bone health of cancer survivors in Korea. This study was designed to measure the prevalence of osteoporosis and to assess related factors among Korean cancer survivors. Materials and Methods: This study was designed as a cross-sectional analysis. Data were obtained from dual energy X-ray absorptiometry measurement of the lumbar vertebrae and femoral neck, and from standardized questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…reported a higher trend of osteopenia and osteoporosis in patients aged 50 years old or younger [ 4 ]. Another study found a higher prevalence of osteoporosis among older cancer survivors, as seen in our patients [ 5 ]. Various factors that may influence BMD in cancer patients were reported in different studies.…”
Section: To the Editors Of The Pan African Medical Journalsupporting
confidence: 82%
See 1 more Smart Citation
“…reported a higher trend of osteopenia and osteoporosis in patients aged 50 years old or younger [ 4 ]. Another study found a higher prevalence of osteoporosis among older cancer survivors, as seen in our patients [ 5 ]. Various factors that may influence BMD in cancer patients were reported in different studies.…”
Section: To the Editors Of The Pan African Medical Journalsupporting
confidence: 82%
“…showed a higher prevalence of osteoporosis among older age, female gender, and lower monthly income cancer survivors. Additionally, being underweight and inadequate calcium consumption in male cancer survivors were associated with osteoporosis [ 5 ]. In our analysis, older age, chemotherapy use, and low level of vitamin D were significantly associated with the prevalence of osteoporosis and osteopenia.…”
Section: To the Editors Of The Pan African Medical Journalmentioning
confidence: 99%
“…KNHANES is a cross-sectional survey that consists of a health interview, a health behavior questionnaire, a health examination, and a nutrition survey for the general population of Korea (11, 12, 13, 14). KNHANES subjects include a representative national sample of the Korean population who were selected using a complex, stratified, multistage probability cluster sampling design (12, 13, 14). Participants in KNHANES are non-institutionalized civilians.…”
Section: Methodsmentioning
confidence: 99%
“…4 In our study, the mean age of patients was 60.15± 12.26 years (range 29-83 years), and a higher prevalence of osteopenia and osteoporosis was seen in patients aged ≥ 60 years compared to ≤ 60 years and the difference was statistically significant. Other studies found a higher prevalence of osteoporosis among older cancer survivors [14,15]. In contrast, AlAmri et al reported a higher trend of osteopenia and osteoporosis in patients aged 50 years old or younger (65.6% vs. 56.4%, P = 0.001) [6].…”
Section: Discussionmentioning
confidence: 86%
“…A study by Choi et al evaluated the prevalence and osteoporosis-associated factors among 556 Korean cancer survivors and compared them to 17,623 non-cancer participants. The results showed that older age, female gender, and lower monthly income in cancer survivors were associated with a higher prevalence of osteoporosis while being underweight and inadequate calcium consumption in male cancer survivors were also linked to the condition [14]. Go groups.…”
Section: Discussionmentioning
confidence: 96%